Principles of spread-spectrum communication systems - Torrieri, Don (Springer International Publishing Imprint: Springer, 2015)
This book provides a concise but lucid explanation of the fundamentals of spread-spectrum systems with an emphasis on theoretical principles. The choice of specific topics is tempered by the author's judgment of their practical significance and interest to both researchers and system designers. The book contains many improved derivations of the classical theory and presents the latest research results that bring the reader to the frontier of the field. This third edition includes new coverage of topics such as CDMA networks, acquisition and synchronization in DS-CDMA cellular networks, hopsets for FH-CDMA ad hoc networks, implications of information theory, the central limit theorem, the power spectral density of FH/CPM complex envelopes, adaptive filters, and adaptive arrays.   ·         Focuses on the fundamentals of spread-spectrum communication systems and provides current examples of their applications ·         Includes problem sets at the end of each chapter to assist readers in consolidating their knowledge and to provide practice in analytical techniques ·         Includes new chapters on adaptive arrays and filters and on ad hoc and cellular code-division multiple-access networks Supplementary material to this book can be accessed at http://link.springer.com/book/10.1007/978-3-319-14096-4.